Personality in the educational space of modernity: priorities and vectors of development - Olena Marchenko (Cхід)
Based on the analysis of theoretical and philosophical orientation of philosophical and educational thought at the end of XIX - beginning of the twentieth century, established mechanisms for determining the socio-cultural and specific historical features of the formation of personality in the educational space of Modernity.